Development of Contextual Learning Media Lubaku (Calculation Hole) in Mathematics Learning at Elementary School - Putri, Dini Aulia Apriansyah; Wati, Dita Prihatna (FKIP - Universitas Riau, 2025)
This research aims to develop a contextual learning media called Lubaku (Calculation Hole) specifically designed to help fourth-grade students at Baru 06 Elementary School understand the concepts of multiplication, division, and squares. This research is classified as research and development using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at Baru 06 Elementary School with a test group of 24 students from class IV B. Data collection techniques were carried out through validation questionnaires involving media experts, material experts, and response questionnaires from students. The data obtained were then analyzed using quantitative and qualitative approaches. The research results show that the Lubaku learning media has been successfully developed. Based on the validation results, this media received an average score of 96% and an average score of 96% from subject matter experts. Additionally, the response from students towards the Lubaku learning media was also very positive, with an average score of 88%. Therefore, overall, it falls into the